2021
DOI: 10.48550/arxiv.2102.11101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

$γγ$ decay as a probe of neutrinoless $ββ$ decay nuclear matrix elements

B. Romeo,
J. Menéndez,
C. Peña

Abstract: We study double gamma (γγ) decay nuclear matrix elements (NMEs) for a wide range of nuclei from titanium to xenon, and explore their relation to neutrinoless double-beta (0νββ) NMEs. To favor the comparison, we focus on double-magnetic dipole transitions in the final ββ nuclei, in particular the γγ decay of the double isobaric analog of the initial ββ state into the ground state. For the most probable decay with equal-energy photons, our large-scale nuclear shell model results show a good linear correlation be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, if and to what extent 0νββ-decay NMEs need to be corrected remains an open question [5,38]. A complementary avenue is to use nuclear physics experiments to constrain the NMEs [39][40][41][42][43][44], but observables well correlated with 0νββ decay are also hard to access [45,46]. In sum, NME uncertainties complicate the extraction of additional physics information from 0νββ-decay experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, if and to what extent 0νββ-decay NMEs need to be corrected remains an open question [5,38]. A complementary avenue is to use nuclear physics experiments to constrain the NMEs [39][40][41][42][43][44], but observables well correlated with 0νββ decay are also hard to access [45,46]. In sum, NME uncertainties complicate the extraction of additional physics information from 0νββ-decay experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic decays connect states in the same nucleus, so that a relation with 0νββ decay can only be expected in the final ββ-decay system, when the initial state is the double isobaric analogue -the state with the same nuclear structure but rotated in isospin space -of the initial ββ-decay state. A recent study finds a linear correlation between γγ magnetic dipole and 0νββ-decay NMEs in the shell model framework (Romeo et al, 2021), opening the door to exploring 0νββ decay with nuclear spectroscopy.…”
Section: E Connections To Nuclear Structure Measurementsmentioning
confidence: 99%
“…However, pairing energy is not observable, this correlation cannot provide a model-independent way to constraint the NME directly. In recent years, Shimizu et al [376] and Romeo et al [379] demonstrated that there is a rather strong correlation between the NMEs of 0νββ decays M 0ν with the ground-state-to-ground-state double Gamow-Teller (DGT) transition strength M DGT…”
Section: Constraints With Correlation Relationsmentioning
confidence: 99%